2021
DOI: 10.3390/microorganisms9061129
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Helicobacter pylori Infection and Laryngeal Cancer-Case Series and a Systematic Review

Abstract: Helicobacter pylori (H. pylori) infection involves the development of gastric cancer and may be associated with laryngeal cancer. However, laryngeal H. pylori infection in Taiwanese patients with newly diagnosed laryngeal cancer has not been reported. This study was aimed to investigate the possible association between laryngeal H. pylori infection and laryngeal cancer in Taiwan and perform a systematic review of previous reports in other countries. An analysis of 105 patients with laryngeal lesions found the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(133 reference statements)
1
1
0
Order By: Relevance
“…In this study, we found that more than 90% of LC patients were over 50 years old or had squamous cell carcinoma (Table 1), which was consistent with some previous studies [31]. Moreover, LNM was more common among males than females (Table 1), which matches the overall sex-based incidence of LC and may be associated with higher smoking and drinking rates in males [32]. Mutlu et al found that the incidence of cervical metastasis occurring in supraglottic tumours was signifcantly higher than that in transglottic tumours (55.2% and 35.1%, respectively) [33], which was similar to our results that the occurrence proportion of LNM was highest in the supraglottic region (Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found that more than 90% of LC patients were over 50 years old or had squamous cell carcinoma (Table 1), which was consistent with some previous studies [31]. Moreover, LNM was more common among males than females (Table 1), which matches the overall sex-based incidence of LC and may be associated with higher smoking and drinking rates in males [32]. Mutlu et al found that the incidence of cervical metastasis occurring in supraglottic tumours was signifcantly higher than that in transglottic tumours (55.2% and 35.1%, respectively) [33], which was similar to our results that the occurrence proportion of LNM was highest in the supraglottic region (Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…LSCC is responsible for ~ 98% of all laryngeal cancers [ 1 ]. Etiological factors for LSCC are diverse and include genetic background, environmental factors, alcohol consumption, cigarette smoking, and viral infections [ 2 ]. Approximately 1.8 million new cases and 1 million deaths of LSCC occur worldwide per year [ 3 ].…”
Section: Introductionmentioning
confidence: 99%